Accession Site Does Not Influence the Risk of Stroke after Diagnostic Coronary Angiography or Intervention: Results from a Large Prospective Registry - Matějka, Jan; Ivo, Varvařovský; Jan, Tužil; Tomáš, Doležal; Martin, Bobák; Pospíchal, Jan; Geier, Petr; Jiří, Vondrák; Karel, Bláha; Jan, Málek; Alena, Staňková; Juraj, Bujdák; et al. (My University, 2021)
Introduction: Periprocedural stroke represents a rare but serious complication of cardiac catheterization. Pooled data from randomized trials evaluating the risk of stroke following cardiac catheterization via transradial versus transfemoral access showed no difference. On the other hand, a significant difference in stroke rates favoring transradial access was found in a recent meta-analysis of observational studies. Our aim was to determine if there is a difference in stroke risk after transradial versus transfemoral catheterization within a contemporary real-world registry. Methods: Data from 14,139 patients included in a single-center prospective registry between 2009 and 2016 were used to determine the odds of periprocedural transient ischemic attack (TIA) and stroke for radial versus femoral catheterization via multivariate logistic regression with Firth's correction. Results: A total of 10,931 patients underwent transradial and 3,208 underwent transfemoral catheterization. Periprocedural TIA/stroke occurred in 41 (0.29%) patients. Age was the only significant predictor of TIA/stroke in multivariate analysis, with each additional year representing an odds ratio (OR) = 1.09 (CI 1.05-1.13, p < 0.000). The choice of accession site had no impact on the risk of periprocedural TIA/stroke (OR = 0.81; CI 0.38-1.72, p = 0.577). Conclusion: Observational data from a large prospective registry indicate that accession site has no influence on the risk of periprocedural TIA/stroke after cardiac catheterization. Keywords: Cardiac catheterization; Femoral access; Radial access; Stroke; Transient ischemic attack.
Místo vstupu neovlivňuje riziko cévní mozkové příhody po diagnostické koronární agniografii nebo intervenci: výsledky z velkého prospektivního registru
Keywords: stroke; transient ischemic attack; cardiac catheterization; femoral access; radial access; cévní mozková příhoda; Transientní ischemická ataka; srdeční katetrizace; femorální přístup; radiální přístup